Evaluation of the Anterior Segment Angle-to-Angle Scan of Cirrus High-Definition Optical Coherence Tomography and Comparison With Gonioscopy and With the Visante OCT - Tun, Tin A.; Baskaran, Mani; Tan, Shayne S.; Perera, Shamira A.; Aung, Tin; Husain, Rahat (Investigative ophthalmology & visual science, 2017)
To evaluate the diagnostic performance of the anterior segment angle-to-angle scan of the Cirrus high-definition optical coherence tomography (HD-OCT) in detecting eyes with closed angles. All subjects underwent dark-room gonioscopy by an ophthalmologist. A technician performed anterior segment imaging with Cirrus (n = 202) and Visante OCT (n = 85) under dark-room conditions. All eyes were categorized by two masked graders as per number of closed quadrants. Each quadrant of anterior chamber angle was categorized as a closed angle if posterior trabecular meshwork could not be seen on gonioscopy or if there was any irido-corneal contact anterior to scleral spur in Cirrus and Visante images. An eye was graded as having a closed angle if two or more quadrants were closed. Agreement and area under the curve (AUC) were performed. There were 50 (24.8%) eyes with closed angles. The agreements of closed-angle diagnosis (by eye) between Cirrus HD-OCT and gonioscopy (k = 0.59; 95% confidence interval (CI) 0.45-0.72; AC1 = 0.76) and between Cirrus and Visante OCT (k = 0.65; 95% CI 0.48-0.82, AC1 = 0.77) were moderate. The AUC for diagnosing the eye with gonioscopic closed angle by Cirrus HD-OCT was good (AUC = 0.86; sensitivity = 83.33; specificity = 77.78). The diagnostic performance of Cirrus HD-OCT in detecting the eyes with closed angles was similar to that of Visante (AUC 0.87 vs. 0.9, respectively; P = 0.51). The anterior segment angle-to-angle scans of Cirrus HD-OCT demonstrated similar diagnostic performance as Visante in detecting gonioscopic closed angles. The agreement between Cirrus and gonioscopy for detecting eyes with closed angles was moderate.